Study of hypocalcemia and its risk factors in post thyroidectomy among a sample of Iraqi patients - Hassan, Ahmed Nafi; Surriah, Mohammed Hillu; Bakkour, Amine Mohammed (International Surgery Journal, 2018)
Background: Hypocalcemia is a well-recognized complication of thyroid surgery. The aim of this study was to determine the incidence of hypocalcemia after thyroid surgery and find out the risk factors involved regarding the patient age, gender, muscular build, clinical diagnosis, extent of surgery, ligation of the inferior thyroid artery, and pathology report. Methods: This prospective study was carried out on 50 patients who underwent thyroid surgery for various thyroid diseases at the surgical department of Karama teaching hospital for the period between January 2016 to July 2016. Serial serum calcium measurements were recorded as well as details of the operation, patient age and gender, ligation of the inferior thyroid artery or not, pathological report. Hypocalcemia was considered transient if it was resolved within 6months and permanent if it persist after 6months and the patient was maintained on supplementation therapy of calcium and vitamin D. Results: Author found that the incidence of post-thyroidectomy hypocalcemia was 30% and in the majority of the cases (24%) was transient, while it was permanent in only (6%) of cases and had occurred mainly after total thyroidectomy and in cases with ligation of the inferior thyroid artery. Conclusions: Author concluded that post thyroidectomy hypocalcemia is a relatively common complication but it is transient in the majority of the patients. Its incidence is related to the extent of the surgery and can be reduced by the good preparation of the patient preoperatively.